Innovation of Moringa Leaves into Pudding as Healthy and Nutritious Dessert - Nur Halim; Mohamad Ikbal Riski A. Danial; Herawan Hisanan; Agus Syam; Muhammad Jufri (PT. Global Research Collaboration, 2025)
Local food innovation based on natural ingredients is increasingly needed to support people's healthy lifestyles. One of the great potentials that has not been exploited optimally is Moringa oleifera leaves, which are known to have high nutritional content such as protein, calcium, vitamin A and antioxidants. This research aims to develop an innovative product in the form of Moripudding, namely a healthy and nutritious pudding made from Moringa leaves, as an alternative dessert that is not only delicious, but also healthy. The method used in this research was to carry out trials through several friends with the optimal composition of Moringa leaves, low-fat milk, gelatin, and natural sweeteners such as honey, as well as organoleptic tests on taste, texture, aroma and color. Initial results show that Moripudding was well received by the panelists, with an average score above 80% for all aspects of the sensory assessment. Apart from that, nutritional content tests show that Moripudding has superior nutritional value compared to conventional pudding, especially in protein and vitamin A levels. This product also has the potential to be developed commercially because the raw material for Moringa leaves is easy to obtain and cheap. With the presence of Moripudding, it is hoped that people will be more open to consuming healthy food based on local plants. This innovation not only supports a healthy lifestyle, but also encourages the use of local biological riches to create food products with high selling value.